Direct transpedal pressure measurement during transpedal below‐the‐knee interventions in critical limb ischemia. Issue 4 (29th June 2020) - Ruzsa, Zoltán; Csavajda, Ádám; Deák, Mónika; Viktor, Óriás; Hizoh, István; Nemes, Balázs; Bertrand, Olivier F; Merkely, Béla; Kwan, Tak W.
Abstract: Aim: The aim of this study was to assess the feasibility of the distal pressure measurement during transpedal below‐the‐knee interventions in chronic limb‐threatening ischemia (CLTI) and to assess the hemodynamic response after percutaneous transluminal angioplasty. Methods: The clinical and angiographic data of 137 consecutive patients treated via transpedal access in CLTI (Rutherford 4–6) were evaluated. Distal pedal pressure (PP) at the end of the pedal sheath was measured and the pedal‐to‐aortic pressure index (PAPI) was also calculated before and after the intervention. Results: Good angiographic results was achieved in 131 patients (95.6%) in the femoro‐popliteal and at least in one below‐the‐knee artery. Significant differences were found in PP and PAPI between before‐ and after‐intervention values (103.2 ± 41.6 mmHg vs. 138.2 ± 37.8 mmHg and 0.74 ± 0.29 vs. 1.03 ± 0.34), respectively. Post‐procedural PP and PAPI were significantly higher in patients who underwent good and borderline/unsuccessful intervention 141.7 [135.8–147.6] versus 82.6 [33.8–131.5] mmHg and 1.05 [1–1.1] versus 0.53 [0.2–0.8], respectively. PP's are significantly different in various Rutherford classification groups. Among the studied parameters, postprocedural PAPI was found to have the best discriminatory power to predict 3‐month amputation (c‐statistic: 0.749, 95% CI: 0.546–0.952, p = .016, sensitivity: 57.1%, specificity: 92.3% using the cut‐off criterion ≤0.58). Major adverse event was detected in 17 patients at 3 months follow up (12.4%), including 7 major amputations (5.1%). Conclusion: Transpedal pressure and pedal‐to‐aortic pressure index significantly increased during transpedal below‐the‐knee angioplasty and final pressure and index correlates significantly with limb salvage.